2011
DOI: 10.1108/09513541111100134
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of school leadership on pupil outcomes

Abstract: Purpose-This study aims to explore the impact of school leadership, particularly that of the principal (head teacher), on school improvement in England. Design/methodology/approach-The study adopts a mixed-methods (MM), longitudinal design to investigate the leadership of a sample of academically effective and improving schools identified from analyses of national assessment and examination data sets. In addition, questionnaire surveys of principals and key staff and 20 qualitative school case studies were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
16

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 15 publications
4
24
0
16
Order By: Relevance
“…The positive impact of strong leadership on student learning through building supportive school culture and creating favourable working conditions for teachers is well documented in the teacher development, school improvement and school effectiveness literature (Hallinger, 2005;Johnson, 2004;Leithwood et al, 2004 andGu et al, 2008;Day et al, 2011;Sammons et al, 2011). There is also evidence which points to strong and positive associations between school leaders' administrative support and low teacher retention rates (Ladd, 2009;Boyd et al, 2011).…”
Section: Teacher Retention: Quality Mattersmentioning
confidence: 99%
See 3 more Smart Citations
“…The positive impact of strong leadership on student learning through building supportive school culture and creating favourable working conditions for teachers is well documented in the teacher development, school improvement and school effectiveness literature (Hallinger, 2005;Johnson, 2004;Leithwood et al, 2004 andGu et al, 2008;Day et al, 2011;Sammons et al, 2011). There is also evidence which points to strong and positive associations between school leaders' administrative support and low teacher retention rates (Ladd, 2009;Boyd et al, 2011).…”
Section: Teacher Retention: Quality Mattersmentioning
confidence: 99%
“…There is also abundant evidence that trusting relationships between the head and their staff are a key feature of successful schools (e.g. Bryk et al, 2010;Day et al, 2011). In their work on successful urban schools, Bryk and Schneider (2002) found that 'teachers who perceive benevolent intentions on the part of their principal are more likely to feel efficacious in their jobs ' (2002, p. 29).…”
Section: Building Relational Resilience With Leadersmentioning
confidence: 99%
See 2 more Smart Citations
“…Reconstruction of organization, setting, directions for subordinates, and motivating and developing people are the common practices of successful principals (Jacobson, 2011). Therefore, school leaders directly or indirectly affect the various aspects of school and classroom process along with academic performance (Sammons, Gu, Day and Ko, 2011). Each of the style (autocratic, democratic, and free-rein) may have benefits as well limitations.…”
Section: Introductionmentioning
confidence: 99%